The frequency of allelic variants of the VDR gene and the level vitamin D in children under one year old in the Kazakh population - Akmaral Zhumalina; Balash Tussupkaliyev; Svetlana Sakhanova; Irina Kim; Mairamkul Zharlykassinova (National Scientific Medical Center, 2023)
Introduction: The study of the genetic aspects of bone metabolism disorders in children is a theoretical and practical interest for pediatrics, especially according to the age and ethnic positions. There is a number of gene polymorphisms (primarily the vitamin D receptor (VDR) gene) that determine the norm and pathology of bone tissue formation. Calcium absorption worsens when there is no functional VDR and active forms of vitamin D. As a result the level of bone mineralization decreases. In children such disorders lead to the development of osteopenia. Objective: To determine the frequency of allelic variants of the VDR gene (rs1544410, rs2228570) and to evaluate its relationship with the level of vitamin D in children under one year old in the Kazakh population. Material and methods: 197 children under one year of age were examined for vitamin D by electrochemiluminescent immunoassay and genotyping of the VDR polymorphism (rs1544410, rs2228570) by PCR. Results: It was found out that children with the C allele of the VDR rs2228570 gene have a reduced level of vitamin D by 1.84 times (95% CI 1.10 - 3.07) and CC - by 2.3 times compared with children with normal vitamin D levels. Statistical analysis by the Kruskal-Wallis method showed that the serum level of vitamin D in AA carriers for the VDR rs1544410 was significantly reduced comparing to the level in GG and GA carriers (p=0.03). Conclusion: The study confirms the need for further in-depth study of the genetic aspects of bone metabolism disorders in children for the development of personalized medicine.